The Role Of Parents In Supporting The Islamic Education Of Young Children In The Digital - Rahmi Yolanda; Zulmi, Fadhli; Nasution, Soibatul Aslamiah; Burhanudin, Burhanudin; Zeky, Serpuadi (Journal of Islamic Early Childhood Education, 2025)
This study aims to describe the role of parents in supporting early childhood Islamic education in the digital age, particularly at Ha-Kasumi Ophir Luhak Nan Duo Kindergarten, West Pasaman. The background of this study is based on the phenomenon of increasing use of digital media among early childhood, which has both positive and negative impacts on their development. The research method used is qualitative research, specifically a case study. The results of the study show that the role of parents at Hakasumi Ophir Kindergarten includes: as educators, parents accustom children to performing worship and reading prayers; as supervisors, parents control the use of cell phones and limit access to inappropriate content; as motivators, parents provide motivation and Islamic role models in everyday life. Although there are challenges in the form of potential gadget addiction and the negative influence of digital media, parents are able to overcome them with an Islamic approach and good communication with their children. As facilitators, parents provide supporting tools such as Islamic books and learning applications. This study confirms that parental involvement has a significant influence on the success of Islamic education for early childhood in the digital era. This study also recommends the need for synergy between parents and schools in building an Islamic learning environment that is adaptive and wise to technological developments.